Hello There! Sorry for the late answer, but better late than never as they say! The correct answer to your query is B: A= F divided by m. Please tell me if this helps any or not.
Answer:
![5h^3- h - 3](https://tex.z-dn.net/?f=5h%5E3-%20h%20-%203)
Step-by-step explanation:
Given
![(2h^3 + 6h) + (3h^3 - 7h - 3)](https://tex.z-dn.net/?f=%282h%5E3%20%2B%206h%29%20%2B%20%283h%5E3%20-%207h%20-%203%29)
Required
Standard form
We have:
![(2h^3 + 6h) + (3h^3 - 7h - 3)](https://tex.z-dn.net/?f=%282h%5E3%20%2B%206h%29%20%2B%20%283h%5E3%20-%207h%20-%203%29)
Remove bracket
![(2h^3 + 6h) + (3h^3 - 7h - 3) =2h^3 + 6h + 3h^3 - 7h - 3](https://tex.z-dn.net/?f=%282h%5E3%20%2B%206h%29%20%2B%20%283h%5E3%20-%207h%20-%203%29%20%3D2h%5E3%20%2B%206h%20%2B%203h%5E3%20-%207h%20-%203)
Collect like terms
![(2h^3 + 6h) + (3h^3 - 7h - 3) =2h^3 + 3h^3+ 6h - 7h - 3](https://tex.z-dn.net/?f=%282h%5E3%20%2B%206h%29%20%2B%20%283h%5E3%20-%207h%20-%203%29%20%3D2h%5E3%20%2B%203h%5E3%2B%206h%20%20-%207h%20-%203)
![(2h^3 + 6h) + (3h^3 - 7h - 3) = 5h^3- h - 3](https://tex.z-dn.net/?f=%282h%5E3%20%2B%206h%29%20%2B%20%283h%5E3%20-%207h%20-%203%29%20%3D%205h%5E3-%20h%20-%203)
Hence, the standard form is:
![5h^3- h - 3](https://tex.z-dn.net/?f=5h%5E3-%20h%20-%203)
Answer:
a₁ = 6
Step-by-step explanation:
The sum to n terms of a geometric sequence is
= ![\frac{a_{1}(r^{n}-1) }{r-1}](https://tex.z-dn.net/?f=%5Cfrac%7Ba_%7B1%7D%28r%5E%7Bn%7D-1%29%20%20%7D%7Br-1%7D)
where a₁ is the first term and r the common ratio
Here
= 1530 and r = 2, thus
= 1530 , that is
a₁ (256 - 1) = 1530
255a₁ = 1530 ( divide both sides by 255 )
a₁ = 6